Frequency of Perforated Appendix During Appendecectomy - Iftikhar Ahmed, Saira Mahmood, Asma Bibi, Memoona Javed, Altaf Hussain Jatoi, Fahad Hafeez Khan, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: The acute appendicitis is commonest surgical emergency in world; there is growing awareness about the significant morbidity and mortality of perforated appendix. We performed this study to determine the frequency of perforation in acute appendicitis in our set up. Methods: Total patients included were 100 in this cross sectional study. All patients were above 14 year of age, both gender who were assessed by history, physical examination and relevant investigations undergoing appendectomy for acute appendicitis. Results: Total number of patient with perforation were 26 (26%) out of 100 operated for appendectomies. All the patients were above 14 years of age. Frequency of perforation of appendix was different according to the age, sex, time of presentation, and TLC count. Conclusion: In order to reduce high percentage of perforated appendix, steps should be taken to sensitize the patients to present early, early referral to surgeons, for quick diagnosis and urgent treatment. Keywords: Acute appendicitis, perforated appendix, appendectomy, appendicular mass.